Evaluation of Time Management in the 6-Storey Polyclinic Building Project of QIM Batang Hospital Using the CPM Method - Jamal, Jamal; Nisa, Fitri Khoirun; Prasetyo, Rendy (Portal: Jurnal Teknik Sipil, 2025)
Project time management is the process of planning, organizing and controlling the schedule of project activities. Time management is needed in a project implementation so that the project can run exactly according to the predetermined time. Scheduling is part of controlling time management. Along with the development of technology and science, project scheduling methods are also developing. One of the scheduling methods that is often used is the Critical Path Method, which is a technique of analyzing the activity network to predict the total duration. This research focuses on evaluating time management on the Batang QIM Hospital Polyclinic Building Project with the CPM method to find out the work that crosses the critical path. In the implementation of the Batang QIM Hospital Polyclinic project, several obstacles were encountered which resulted in the delay of work causing the project to be late. These obstacles include labor, materials, and weather. From the analysis that has been done based on the schedule plan that has been made before there are 7 types of work that cross the critical path. The total project duration required after using the CPM method is 43 weeks or one week earlier than the planned schedule of 44 weeks.